(untitled) (Revista Direito em Debate, 2023)
This work has the general objective to present the main principles and themes related to privacy, covering the main aspects of the law of data protection, corruption and the responsibility of the administrators, presenting some examples regarding data leakage. The specific objective is to analyze the applicability of the Compliance Program that companies must follow in order to comply with the requirements imposed by the General Law of Data Protection, Law 13709/2018 ("LGPD"). The methodology used was the bibliographical research on the subject, by the scientific articles, doctrines, legal journals, manuals and periodicals, besides specific legislation and jurisprudence.